1991
DOI: 10.1111/j.1360-0443.1991.tb01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Control versus abstinence in the treatment of pathological gambling: a two to nine year follow‐up

Abstract: A structured gambling interview schedule, the Eysenck Personality Questionnaire, Spielberger's State-Trait Anxiety Inventory, Zuckerman's Sensation Seeking Scale and Beck Depression Inventory were administered to 63 out of 120 pathological gamblers who had 5 years previously completed a behavioural treatment for uncontrollable gambling behaviour. Results indicated that both abstinence and controlled gambling outcomes were associated with continued improvement in self-report and psychological indices of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 24 publications
1
47
1
4
Order By: Relevance
“…Moreover, research has demonstrated the viability of moderation treatment goals-most often for alcohol use and gambling disorders than for illicit substance use disorders-and has suggested that offering these goals might provide a more realistic, attractive option for clients, and might lead to lower attrition rates by increasing self-efficacy and motivation early in treatment (Blaszczynski, McConaghy, & Frankova, 1991;Booth, Dale, & Ansari, 1984;Ladouceur, Lachance, & Fournier, 2009;Marlatt & Donovan, 2005;. Beyond a client merely having a moderation goal in treatment, moderation-focused treatments for alcohol use and gambling disorders have been specifically developed and tested that help clients work explicitly towards moderation goals and that incorporate moderation-focused techniques (Dowling, Smith, & Thomas, 2009;Ladouceur et al, 2009;Marlatt & Witkiewitz, 2002;Saladin & Santa Ana, 2004).…”
Section: Overview In the Addictive Disorders Literaturementioning
confidence: 99%
“…Moreover, research has demonstrated the viability of moderation treatment goals-most often for alcohol use and gambling disorders than for illicit substance use disorders-and has suggested that offering these goals might provide a more realistic, attractive option for clients, and might lead to lower attrition rates by increasing self-efficacy and motivation early in treatment (Blaszczynski, McConaghy, & Frankova, 1991;Booth, Dale, & Ansari, 1984;Ladouceur, Lachance, & Fournier, 2009;Marlatt & Donovan, 2005;. Beyond a client merely having a moderation goal in treatment, moderation-focused treatments for alcohol use and gambling disorders have been specifically developed and tested that help clients work explicitly towards moderation goals and that incorporate moderation-focused techniques (Dowling, Smith, & Thomas, 2009;Ladouceur et al, 2009;Marlatt & Witkiewitz, 2002;Saladin & Santa Ana, 2004).…”
Section: Overview In the Addictive Disorders Literaturementioning
confidence: 99%
“…Marlatt (2002) utilised Buddhist 'middle-way' philosophy that discourages the behavioural extremes of both over-indulgence and total abstinence. Whilst problem gambling treatments tend to be abstinence orientated (Walsh et al, 2007), 'controlled gambling' can exert a strong preventative influence over relapse and lead to continued improvements in levels of arousal, anxiety, and depression (Blaszczynski, McConaghy & Frankoya, 1991).…”
Section: Conflict: Self-compassion Compassion and 'Spiritual Nourismentioning
confidence: 99%
“…Participants were encouraged to view the feedback as a tool for making informed choices. Evidence suggests that subjects who engage in controlled gambling after treatment fare as well as those who abstain completely (Blasczynski et al, 1991), and we did not impose a requirement to stop gambling. However, it was emphasized that abstaining or gambling in moderation can minimize harm experienced as a consequence of gambling.…”
Section: Brief Secondary Prevention Programmentioning
confidence: 99%